Formulation and evaluation of compression Coated tablets of Lornoxicam for Targeting early morning peak symptoms of Rheumatoid arthritis - Hadi, Mohd Abdul; Rao, NG Raghavendra; Rao, A Srinivasa (Dhaka University Journal of Pharmaceutical Sciences, 2014)
In the present research work, we have designed a pulsatile formulation of lornoxicam to treat rheumatoid arthritis as per the chronotherapeutic pattern of the disease. Core tablets were prepared by incorporating different concentration of disintegrants and were compressed in between different concentration and combination of hydrophobic and hydrophilic polymers. The core and compression coated tablets were subjected to pre-formulation, physicochemical, in-vitro drug release and stability studies. FTIR and DSC studies revealed that there was not any chemical reaction between pure drug lornoxicam and polymers. The pre and post-compressional parameters of tablets were also found to be within limits. The core tablets which were incorporated with 10% of crospovidone were found to be as most fastly disintegrating. Our optimized formulation F-5 releases lornoxicam after a lag time of 5.5±0.7 hours and 99.81±0.81% upto 8 hours. Stability was also found for the optimized formulation according to ICH guidelines. Dhaka Univ. J. Pharm. Sci. 12(2): 109-117, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17620